Educational Implications: Physiological Changes in Eye Movement Desensitization and Reprocessing Treatment for Post-Traumatic Stress Disorder - Herman, Jeffery Scott; Michael, Tony; Hermann-Turner, Katherine (COUNS-EDU: The International Journal of Counseling and Education, 2023)
Despite more than three decades of research, the educational community's understanding of the mechanisms underlying Eye Movement Desensitization and Reprocessing treatment remains incomplete. This article critically examines the existing literature, focusing on the physiological mechanisms present when Eye Movement Desensitization and Reprocessing therapy is successfully administered. The review encompasses various research methodologies, including neuroimaging investigations tracking volumetric changes, shifts in relative brain activity across regions, and electroencephalographical alterations in brain function. Through this exploration, the authors underscore the necessity for future studies that delve into the mechanisms of action within children and adolescents and the transformations associated with treating complex post-traumatic stress disorder. The article will identify gaps in knowledge, emphasizing implications for educators and educational practices. A deeper understanding of these phenomena will provide insights for educators and the approaches used to address trauma-related issues in educational settings.